1986
DOI: 10.1021/jm00154a009
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanism of interaction of 10-propargyl-5,8-dideazafolate with thymidylate synthase

Abstract: The interaction of Lactobacillus casei thymidylate synthase (TS) with 10-propargyl-5,8-dideazafolate (NPQ) in the presence of 2'-deoxyuridylate (dUMP) has been investigated. After formation of a rapidly reversible dUMP-NPQ-enzyme complex, a slow isomerization occurs to provide a ternary complex that can be isolated on nitrocellulose membranes or by gel filtration. Unusual features of the isolable complex are the slow rate by which it is formed (t1/2 = 0.88 h) and the slow rate at which it dissociates (t1/2 = 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 5 publications
2
60
0
Order By: Relevance
“…The purification procedures of wild-type and mutant TSs were carried out as described previously (30,32). TS activity was monitored by a spectrophotometric assay as described previously (33,34). Methods for measurement of k cat values, the Michaelis constants (K m values) for CH 2 H 4 folate and dUMP and inhibition constants (K i values) for raltitrexed, Thymitaq, BW1843U89, and FdUMP were as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
“…The purification procedures of wild-type and mutant TSs were carried out as described previously (30,32). TS activity was monitored by a spectrophotometric assay as described previously (33,34). Methods for measurement of k cat values, the Michaelis constants (K m values) for CH 2 H 4 folate and dUMP and inhibition constants (K i values) for raltitrexed, Thymitaq, BW1843U89, and FdUMP were as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
“…Enzymatic activity was monitored by spectrophotometric assay of the conversion of CH2H4folate to H2folate under previously described conditions (Pogolotti et al, 1986). Assay solutions contained 40 pM dUMP, 100 pM CH2H4folate, and between 0.1 and 0.5 pM enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…That these interactions are sufficiently strong to overcome repulsion between Glu 126' and the dUMP phosphate, as well as to induce the closed protein conformation, points to the usefulness of quinazolinebased TS inhibitors. Indeed, CB3717 has a nanomolar inhibitory constant and an extremely long association half-life (Pogolotti et al, 1986). However, the loss of covalent bond formation in one active site suggests the mutant protein is less able to achieve covalent intermediate I11 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently suggested that the poor density observed for the covalent bond between Cys 146 and nucleotide in this and other complexes may reflect a weak or polarized bond during catalysis that is required to help the enzyme I rotate out of the active site to relieve electrostatic repulsion with the dUMP phosphate, yet the R126E mutant was -2000-fold less active than wild-type TS. Two crystal structures of R126E were obtained: the first from crystals grown in the presence of dUMP, and the second in the presence of dUMP and CB3717, an analog of CH2THF that displays a nanomolar inhibition constant (Jones et al, 1981;Pogolotti et al, 1986). In both proteins, Glu 126' occupied the same position as Arg 126' in the wild-type protein, resulting in not only electrostatic, but also steric interference with the dUMP phosphate.…”
Section: I1mentioning
confidence: 99%